Virtualizing the real: a virtual reality contemporary sculpture park for children. Issue 2 (3rd July 2018) - Flint, Tom; Hall, Lynne; Stewart, Fiona; Hagan, David
ABSTRACT: This paper discusses a virtual reality experience for a contemporary sculpture park, Jupiter Artland, developed in Minecraft targeting 9–11-year-old children. Issues of fidelity, realism and authenticity are considered, examining the use of Minecraft to create visual representations loosely coupled with reality that generate affective responses. We discuss the build of our virtual sculpture park outlining our approach to creating a facsimile of the sculpture park through adopting practices from the Minecraft community and refining and improving the artworks and experience informed by a class of 9–10 year old children. Using the real and virtual sculpture parks we explore the impact of engaging with the real before the virtual Jupiter Artland and vice versa, with the results from a three class study outlined in this paper.